Cavitation reactor installation for processing hydrocarbon - Tselischev, A.; Loriya, M.; Ijagbuji, A. (Teka Commission of Motorization and Power Industry in Agriculture, 2016)
This paper proposes a new, simple and an efficient method for methanol formation under the cavitation influence of hydrogen-peroxide using a dynamic cavitation reactor. The process involves the reaction of the generated hydroxyl radical with propanebutane gas (C3–C4) to form propyl and butyl radicals which decompose into methyl radicals and alkenes, followed by the subsequent yield of methanol (via the interaction of methyl-radical with hydroxyl radical). Technological process parameters employed in this investigation are quite achievable for industrial production.
Keywords: propane-butane gas; hydroxyl radical; dynamic cavitation; hydrogen peroxide solution